The Participation of Russian Architects and Sculptors in Making the Art Deco Architecture in Serbia - Prosen, Milan (Actual Problems of Theory and History of Art, 2016)
The aim of this paper is to present the participation of Russian artists in the emergence and development of the Art Deco style in Serbian architecture, the style that marked the period between two world wars. In emanations of this style in Serbia, Russian architects and sculptors were of great importance, though their role was not discussed in historiography as a separate phenomenon. The decorative attitude made this essentially modern style more accessible to the refined artistic taste of Serbian social elite, which made Art Deco part of the image of its representative identity. In this period, Belgrade engaged architects arriving from Russia, who followed the local artistic demands, oriented toward decorative but also modern architectural form, and produced significant artistic oeuvre. Art Deco in Serbia was based on the modernization of constructions and building forms, nevertheless focused on façade decoration, enriched with ornaments, stylized reliefs, sculptures and fine-detailed ironwork. Architect and sculptor Roman Verhovskoj interpolated elements of the Art Deco style in an expressive and powerful way. Vladimir Zagorodnjuk decorated many public and apartment buildings with reliefs. ViktorLukomski as the architect of the Yugoslav government designed the Palace of the Patriarchate of the Serbian Orthodox Church, and the State Hotel on Avala mountain. Architects Aleksander Medvedev, Valerij Stashevski, Andrej Papkov and Grigorij Samojlov embraced the style of softened, rhythmical, ornamentally enriched architecture, and developed a specific line of ornamental Art Deco. Creating the elaborate Art Deco interior of Cinema Belgrade, the most elite movie theater in Yugoslav capital, architect Grigorij Samojlov brought the spirit of Hollywood to Belgrade. The interwar development of the city and the quadruple increase in population were followed by the creation of its architectural identity, decisively marked by the modernity of Art Deco, following global trends that put it close to Paris, New York, Madrid, Casablanca, Havana, and Mumbai. In the oeuvre of Russian architects who worked in Serbia between two world wars, we notice a large variety of typical Art Deco motifs. Either contemporary or originating from classical, national, religious or mythological art, they are always transformed in accordance with contemporary modern spirit without direct application of topical templates. Already present in the early, initial phase of the style (1920–1927), related to Exposition Internationale des Arts Décoratifs et Industriels Modernes, held in Paris in 1925, Russian architects and sculptors strongly reflected the new style in the mature stage of its development (1928–1934), adopting both ornamental and sculptural forms of Art Deco. In the 1930s, their involvement in public and private architecture alike intertwined with the activities of local builders, with whom they equally participated in winning markets and personal self-fulfillment. In the late stages of Art Deco style, which in Serbian architecture developed in the period of 1935–1941, the Russian builders expressed the “joie de vivre” spirit characteristic of Art Deco, which became the most explicit form of the positive, creative global connectivity bringing to life some highlights of Serbian architecture.
Keywords: Russian emigrant architects and sculptors; Art Deco architecture; Art Deco reliefs; Serbian architecture in the 1920s and 1930s